Particles for Local Delivery of Proteins Using Intra-Articular Route - Khodabandehlou, Khosrow (Adv Healthc Mater, 2016)
Designing a vehicle for local delivery of proteins using intra-articular route is an attractive option to minimize the adverse effects associated with systemic exposure and to maximize the efficacy. Slowly-dissolving silylated micro-particles are designed with specific size and shape that are capable of extending the retention time of a model protein (BSA) in the murine knee joint. No cytotoxicity is observed for the reconstituted formulation when tested against synovial fibroblasts and RAW macrophages.